2022
DOI: 10.1007/s11524-022-00665-z
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Historical Redlining with Present-Day Neighborhood Environmental and Health Outcomes: A Scoping Review and Conceptual Model

Abstract: Following the Great Depression and related home foreclosures, the federal government established new agencies to facilitate access to affordable home mortgages, including the Home Owners’ Loan Corporation (HOLC) and Federal Housing Administration (FHA). HOLC and FHA directed widespread neighborhood appraisals to determine investment risk, referred to as “redlining,” which took into account residents’ race. Redlining thereby contributed to segregation, disinvestment, and racial inequities in opportunities for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 69 publications
(106 reference statements)
1
78
1
Order By: Relevance
“…Rather, they are reflections on how the federal government reinforced racial and ethnic segregation and the use of race as a significant determinant of property value [7]. HOLC's 1930s formalization of "redlining" was how the federal government supported a diverse set of actors' discriminatory beliefs on race and place which perpetuated racial and ethnic segregation across the US [8]. This provides evidence against de facto residential segregation, and shifts the ensuing impacts (e.g., environmental) onto the institutions themselves (i.e., de jure residential segregation) [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, they are reflections on how the federal government reinforced racial and ethnic segregation and the use of race as a significant determinant of property value [7]. HOLC's 1930s formalization of "redlining" was how the federal government supported a diverse set of actors' discriminatory beliefs on race and place which perpetuated racial and ethnic segregation across the US [8]. This provides evidence against de facto residential segregation, and shifts the ensuing impacts (e.g., environmental) onto the institutions themselves (i.e., de jure residential segregation) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of historical redlining, recent studies have shown associations between redlining and heat stress and higher intra-urban heat [12], less greenspace [13,14], higher incidence of brownfield sites [14], oil and gas well siting [15], and air pollution [8,16]. Poor health is a well-understood consequence of environmental exposures; redlining has also been associated with higher cardiovascular disease risk [17], asthma risk [18], preterm birth [19,20], breast cancer mortality [21], and generally poorer mental and physical health [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Although these grades were assigned nearly 100 years ago, they have a remarkably persistent association with present day environmental conditions [31]. When surveyed in 2020, the grades assigned in the 1930s were associated with significant differences in ambient temperature [32].…”
Section: Redlining and Ambient Temperaturementioning
confidence: 99%
“…When controlling for median household income and proportion of Black residents in Baltimore, MD neighborhoods, Grade D areas are associated with 5.2 years reduction in life expectancy and C-graded areas with 4.9 year reduction [43]. Overall, a recent scoping review found that studies nearly universally reported evidence of an association between redlining and health-relevant outcomes [31].…”
Section: Redlining and Ambient Temperaturementioning
confidence: 99%
“…Urban design, in turn, can further amplify these background climate stressors through the well-known urban heat island and rainfall effects, which are largely controlled by the local dominance of impervious land covers, surface roughness, and lack of mature tree canopy. While the extent to which present-day exposures and outcomes related to these climate-exacerbated environmental risks in urban areas can be linked to historical policies has received recent attention (Mujahid et al 2021;Lane et al 2022;Swope et al 2022), causal inference within observed correlative associations has yet to be established. Here, we use a boundary design to estimate the persistent, causal effects of redlining on present-day exposure to climate change-exacerbated environmental risks in six large U.S. cities.…”
mentioning
confidence: 99%